Evaluation of Low Dose Divalproex Sodium in Night Terror in Adults – A Pilot Study in Indian Patients - Parthasarathy.S; Ravi.S (International Journal of Pharma and Bio Sciences, 2021)
Night terror is a form of parasomnias manifested as sudden arousal with cry and autonomic symptoms. It is commonly reported in children and reported to be rare in adults. There are no clear management strategies for the disease as the pathophysiology is unclear in adults. Studies about its management is limited in literature As Divalproex sodium is effective in parasomnias, we wished to try the same for this indication and find out its efficacy. We included 20 such adult patients with episodes at least twice a month, in a pilot study. All routine investigations, echocardiogram, MRI of the brain and electroencephalography (EEG) were normal in the patients. We started on Divalproex sodium (DIVALID – ER 250 mg- Linux laboratories) as a single dose in the night. The changes in symptomatology and side effects were noted. Results: The mean age was 34.45 ±8.98 years. The male: female ratio was 6:14. All the twenty patients became symptom free as soon as (within three to four days) the drug was started. There were no episodes in the next six months. The drug was stopped in 17 patients with no residual effects. One patient stopped on her own but it was uneventful. In two patients, it was continued as the patients were not very clear about complete recovery of symptoms even-though there were no such episodes. There were no distinct side effects. We conclude that a short six-month course of low dose of Divalproex sodium is effective in giving long term relief in adult patients with night terror.